Evaluation of IT Risk Management in the Banking Industry using the COBIT 2019 Framework - Rahardian, Bram; Raden Venantius Hari Ginardi (Dinasti Review, 2025)
Digital transformation has become a key strategy in the development of modern banking services. However, this process brings various risks that may hinder the achievement of business goals. This study aims to evaluate information technology (IT) risk management at PT. Bank Pembangunan Daerah Jawa Timur Tbk (Bank Jatim) using the COBIT 2019 framework. The main focus is directed at two domains: EDM03 (Ensure Risk Optimisation) and APO12 (Manage Risk). The research was conducted using a qualitative approach and case study method, with observation, interviews, and questionnaires as data collection techniques. The results show that Bank Jatim is currently at Level 2 for the EDM03 domain and Level 3 for the APO12 domain, while the target level for both is Level 4. Several gaps were identified, indicating the need for improvements in IT governance and risk management. Strategic recommendations are provided to support the achievement of optimal and sustainable digital transformation.